BEBERAPA INSEKTISIDA YANG DAPAT DIGUNAKAN SEBAGAI PENGENDALI Aedes Aegypti DI PEMUKIMAN - Hasan Boesri (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
Aedes aegypti have spread throughout every area in this country, with different density level, depends on the height of built houses area. The higher its area the lower density level it has. Aedes aegypti control still become a priority. This was done by applying a thermalfogging method by using the insecticide. Insecticides used (in minimum dosage) in the thermalfogging system which able to kill mosquitoes (up to 100%) are known as: Fendona 30EC dosage 150 ml/ha, Cynoff 25EC dosage 400 ml/ha, Malathion 96EC dosage 400 ml/ha, Icon 25EC dosage 50 ml/ha, resigen 1.5/1 O.OS dosage I00 ml/ha, Malathion 95EC dosage 400 ml/ha, Bistar 12.5 ULV dosage 400 ml/ha, Ciplus 50EC dosage 200 ml/ha, Bistar 25EC dosage I00 ml/ha, Perrnanet IOOEC dosage I 00 ml/ha, Deltacline 25EC dosage 80 ml/ha, Procon 25EC dosage 60 ml/ha, Vectron 95EC dosage 60 ml/ha, Vectron 95EC dosage 60 ml/ha, Seruni I OOEC dosage IO ml/ha. The insecticide spraying against insects will be very useful if used under the right dosage